Sovereign Debt: Indexation and Maturity - Laura Alfaro; Fabio Kanczuk (Inter-American Development Bank, Research Department, 2006)
In this paper we review the literature on sovereign debt with particular emphasis on indexation and maturity and the main policy proposals related to these topics. We also advance some implications derived from our work. In Alfaro and Kanczuk (2005a, b, c), we modeled sovereign debt as a contingent claim following the framework developed by Grossman and Van Huyck (1988). Our framework, however, recognizes that contingent debt might be associated with incentive problems. Applying this framework to the study of the sustainability of sovereign debt, the tradeoff between nominal and indexed debt, and the optimal debt maturity, we find some of the proposals advanced in the literature regarding lengthening debt maturity and issuing nominal debt to be unsustainable in emerging (volatile) economies.
Keywords: 330; Öffentliche Anleihe; Indexanleihe; Fälligkeit; Welt